HF filter design and computer simulation - Rhea, Randall W. (Atlanta, GA Noble Publishing Corporation, 1994)
The book reviews developments in the following fields: network fundamentals; reactors and resonators; transformations; filter losses; computer-aided strategies; lowpass structures; bandpass structures; highpass structures; bandstop structures; and PWB manufacturing.
Also available in print version.
Electronic reproduction.
Keywords: Electric filters -- Design and construction; Electric filters -- Mathematical models; Microwaves -- Mathematical models; Electronic books